The Effects of phonological composition on the memorability of a fabricated name - Lagula, Kristina V.; Castro, Maria Corazon Saturnina A. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
In this day and age of tough competition in the marketing and advertising world, a product name's memorability is one important factor to consider in promoting the product. This is not to say that a product's marketability relies largely on the name's memorability, but is cannot be denied that a good name gives an "edge" - and in the competitive world of endless consumer product promotions and innovations, even the smallest point counts. This research study focuses on how to create that added edge - a name that will stick to mind, a name that will sell. Patterning after the psychology-focused Ebbinghaus tradition of utilizing nonsense syllables in memory work and using models by psychologist Alan Baddeley and psycholinguistics Levelt, et al. on memory and linguists Clark and Yallop on phonology, the study looks at how language, specifically nonsense words are processed in the memory. In effect it aims to find specific sounds that are relatively more memorable, that is, a sound and consequently a name that can be retrieved easily from memory. Aside from this, another focus of the paper is the impact of sounds on the listener. Psycholinguistics such as roger Brown assert that some sounds possess innate characteristics that create either negative images or positive images on a listener's mind. One of the goals of this study then is to distinguish and differentiate which sounds give these negative images and which give other wise. In studying that part of grammar which concentrates on sounds, a science called Phonology, this research attempts to go beyond the transcendental theories and the technicalities bu incorporating language and psychology with the field of brand naming and advertising and putting them in a practical application. This study is therefore a quantitative on in that it resorts to the methods of survey and experiment in looking for these specific sounds that are not only memorable, but which create a positive impact as well.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.